PENGARUH METODE KONSELING TENTANG IUD TERHADAP PENGETAHUAN IBU DI PUSKESMAS KOTA KABUPATEN BANTAENG - Nurhikmah Nurhikmah; Reskiawati Azis; Muliyana; Nur Aliya Arsyad (Universitas Pahlawan Tuanku Tambusai, 2022)
Most pairs of childbearing age do not want to use long-term contraceptive methods such as the IUD. One of the causes is the mother's lack of knowledge regarding IUD contraceptive methods. Health counseling is a process that runs and blends with all aspects of Family Planning services and not just information that is provided and discussed on one occasion, namely at the time of service delivery. The purpose is to find out the influence of counseling about IUD on the knowledge of mothers at the Bantaeng Regency City Health Center. The method of using the research design used is the Cross-Sectional method. The research was conducted in November 2021 at the City Health Center. The population in this study were all acceptors of Family Planning. The sample in this study was acceptors who came to the Family Planning Poly of the City Health Center as many as 33 people using the Acchidental Sampling technique. The results showed that of the 33 respondents used as a sample, before being given health counseling, 10 people (30.3%) were well informed about IUD contraception and 23 people were less knowledgeable (69.7%). After being given well-informed counseling about IUD contraception as many as 27 people (81.8%) and those with less knowledge as many as 6 people (18.2%). Conclusion: counseling methods affect the mother's knowledge of IUD with p-value 0,002 <0,005. Suggestion: It is hoped that midwives who are in charge of the birth control poly section will further improve their performance and attention to acceptors who want to use contraception by actively providing counseling to acceptors so that it is hoped that the coverage of IUD KB acceptors can be achieved according to the target. Keywords: Acceptor, Counseling Methods, IUD, Knowledge